Molecular background of self-incompatibility in apricot - Halász, Júlia; Hegedűs, Attila; Pedryc, Andrzej (Acta Biologica Szegediensis, 2005)
Prunus species show gametophytic self-incompatibility, a trait encoded by a single multiallelic locus, termed S-locus. The S-gene products in styles are pistil ribonucleases, while the pollen component is an F-box protein suggesting that the ubiquitin-mediated protein degradation system has a pivotal role in self/non-self recognition. Using non-equilibrium pH gradient electrophocusing and PCR analysis with several S-gene specific degenerate primer pairs allowed to identify nine new alleles in apricot. Their schematic structure was determined and confirmed to be different from the previously described alleles. Monitoring of different self-(in)compatibility alleles were also successful using a combination of the two techniques. Preliminary results for the molecular background of fruit set behaviour in apricot are discussed.